2021
DOI: 10.1016/j.heliyon.2021.e06330
|View full text |Cite
|
Sign up to set email alerts
|

Environmental health situation in Nigeria: current status and future needs

Abstract: Environmental health-related risks are becoming a primary concern in Nigeria, with diverse environmental problems such as air pollution, water pollution, oil spillage, deforestation, desertification, erosion, and flooding (due to inadequate drainage systems) caused mostly by anthropogenic activities. This paper reviews the pre-existing and current environmental health problems, proffer future research and needs, policy needs, and recommendations necessary to mitigate Nigeria's environmental health situation. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 65 publications
1
30
0
Order By: Relevance
“…Similarly, co-exposure to Pb and Hg among artisanal gold miners has been reported in Bukkuyum Local Government Area of Zamfara State, Nigeria (Rabiu et al 2019). In a more recent study, Pona et al (2021) reported that Pb exposure in Nigeria caused over 2,500 deaths and about 600 thousand disability-adjusted life years (DALYs) lost yearly between 2007 and 2017, with a steady increase in cardiovascular disease and ischaemic heart diseases. Pb toxicity in poultry has also been observed in North-Western Nigeria with concentrations in the tissues ranging between 7.5 mg/kg and 120.5 mg/kg wet weight (Oladipo et al 2020).…”
Section: Level Of Heavy Metals Occurrence In Samplesmentioning
confidence: 84%
See 1 more Smart Citation
“…Similarly, co-exposure to Pb and Hg among artisanal gold miners has been reported in Bukkuyum Local Government Area of Zamfara State, Nigeria (Rabiu et al 2019). In a more recent study, Pona et al (2021) reported that Pb exposure in Nigeria caused over 2,500 deaths and about 600 thousand disability-adjusted life years (DALYs) lost yearly between 2007 and 2017, with a steady increase in cardiovascular disease and ischaemic heart diseases. Pb toxicity in poultry has also been observed in North-Western Nigeria with concentrations in the tissues ranging between 7.5 mg/kg and 120.5 mg/kg wet weight (Oladipo et al 2020).…”
Section: Level Of Heavy Metals Occurrence In Samplesmentioning
confidence: 84%
“…Comparing the levels of heavy metal contamination between regions showed generally higher levels of toxic elements in the central and this occurrence could be probably due to the trace oil exploration activities that regularly pollutes the soils in the region. In addition, illegal artisanal heavy metal mining activities, use of leaded petrol and the dumping of electronic wastes have also been reported to contribute to environmental heavy metal contamination, poultry toxicity and human poisoning in Nigeria (Dooyema et al 2012;Rabiu et al 2019;Oladipo et al 2020;Pona et al 2021). Iftikhar et al (2014) analysed the concentrations of heavy metals in milk samples from urban and rural areas in Pakistan and observed that samples from urban areas had higher levels of the toxic metals.…”
Section: Level Of Heavy Metals Occurrence In Samplesmentioning
confidence: 99%
“…Climate change due to deforestation increased human activity, desertification, wildfires, and traffic leads to the increase of all of these pollutants both indoors and outdoors affecting human health ( 60 ). Additionally, increased temperature due to climate change increases the rate of fungi growth ( 61 ).…”
Section: Health Effects Of Climate Change-induced Environmental Expos...mentioning
confidence: 99%
“…The environment in Nigeria is rapidly degenerating as a result of increased industrialization, use of fuelwood, second-hand vehicle, gas flaring and illegal mining [6]. This review focused on industrial wastewater generation, treatment and disposal by some selected industries in the non-oil sector across Nigeria, with the aim of elucidating the potential hazardous effects of some emerging contaminants associated with such industrial wastewater disposal and making of recommendations for their remediation.…”
Section: Introductionmentioning
confidence: 99%